DIGITAL DICTIONARIES: DEFINITION AND IMPORTANCE (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2025)
Annotation:This article provides an overview of digital dictionaries, discussing their definition, types, significance, and usage in various contexts. The article also addresses the advantages and challenges of digital dictionaries, their role in language learning, and common issues related to their use.